The 5th Asia-Pacific Management Research Conference (APMRC) : “Adapting Sustainability Strategies in Business and Management” (Sciendo, 2024)
The Asia Pacific Management Research Conference (APMRC) is an academic event organized by the PPM School of Management. The implementation of APMRC has experienced developments since the first year, both in terms of the concept of a series of activities, paper assessment categories, and the facilities provided to participants. The year of 2024 marks the 5th APMRC, hosted by PPM School of Management (Indonesia), Widya Dharma Pontianak University (Indonesia), Panca Bhakti University (Indonesia), and Hanoi University of Science and Technology - School of Economics and Management (Vietnam). The aim of the 5th APMRC is to provide a forum for academics and professionals to share research findings, experiences, and knowledge for growth and sustainability in the Asia-Pacific. The research topics presented at the 5th APMRC related to management and economics can include the following derivative topics, but are not limited to Strategic Management, Human Resources/Capital, Operations and Supply Chain, Organizational Behaviour, Innovation and Entrepreneurship, Corporate Governance, Finance and Accounting Management, Risk Management, Marketing Management, Cost Management, Sustainable Business Development, Hospitality and Tourism, Family Business, SME's, and Machine Learning in Business Conference date and place Date : August 21st – 23rd, 2024 – Pontianak, Indonesia Venue : Auditorium 10th Floor, Widya Dharma University, Hos Cokroaminoto St., No.445, Darat Sekip, Kec. Pontianak Kota, Kota Pontianak, Wets Kalimantan, Indonesia, 78243 Article Processing Charge (APC) Lecturer and General: $ 95 Graduate and Undergraduate Student: $ 75 Proceeding Publication Fee: $ 145 Conference Organizer PPM School of Management (Indonesia), in cooperation with Widya Dharma Pontianak University (Indonesia), Panca Bhakti University (Indonesia), and Hanoi University of Science and Technology – School of Economics and Management (Vietnam). Description of The Peer Review Process All manuscripts have gone through'double-blind review'according to COPE (Committee on Publication Ethics) by reviewers and editing by the implementing editor, where both the authors of a manuscript and the reviewers remain anonymous to each other throughout the evaluation, ensuring that neither party can influence the review based on the other's identity, thus minimizing bias. This conference follows the Committee on Publication Ethics (COPE)https://publicationethics.org/ guidelines in dealing with all aspects of publication ethics, especially how to handle cases of research and publication errors. This scientific publication ethics statement is a statement of the code of ethics for all parties involved in the publication process of this scientific journal, namely the manager, editor, reviewers, and authors. The Code of Ethics for Scientific Publications essentially upholds three ethical values in publications, namely (i) Neutrality, namely being free from conflicts of interest in managing publications; (ii) Justice, namely giving authorship rights to those entitled to be authors; and (iii) Honesty, namely free from duplication, fabrication, falsification and plagiarism in publications. Review process 1. The author(s) submit the paper through the link provided in the website of The 5th APMRC 2024 2. The paper is checked for the suitable in scope, writing template, and language by the committee. Those are not suitable are returned to the authors for either resubmission or decline. 3. Two reviewers whose expertise relevant to the topic are assigned to a paper (double blind review). 4. The r